Synergistic Effect of Cefazolin Plus Fosfomycin Against Staphylococcus aureus in vitro and in vivo in an Experimental Galleria mellonella Model - Kussmann, Manuel; Obermueller, Markus; Karer, Matthias; Kriz, Richard; Chen, Rui-Yang; Hohl, Lena; Schneider, Lisa; Burgmann, Heinz; Traby, Ludwig; Vossen, Matthias G. (Frontiers in Pharmacology, 2021)
Objectives: This study investigated the synergistic in vitro and in vivo activity of cefazolin plus fosfomycin against methicillin-susceptible and methicillin-resistant S.aureus (MSSA and MRSA) to provide the basis for a potential treatment alternative. Methods: Antimicrobial susceptibility and in vitro synergy tests were performed with five MSSA and five MRSA isolates using the broth microdilution and chequerboard assays, respectively. The in vivo efficacy of cefazolin plus fosfomycin for the treatment of MRSA infections was assessed using the Galleria mellonella survival assay. Results: Using fractional inhibitory concentration index (FICI), the evaluated combination of cefazolin plus fosfomycin showed synergistic in vitro activity against all MSSA and MRSA isolates tested. In addition, cefazolin susceptibility was recovered in all MRSA isolates except one fosfomycin-resistant strain when combined with fosfomycin at readily achievable concentrations. The G.mellonella survival assay demonstrated highly synergistic in vivo activity of cefazolin plus fosfomycin, resulting in a 44% and 52% reduction in mortality when compared to cefazolin-alone and fosfomycin-alone, respectively. Conclusions: If susceptibility to fosfomycin is either confirmed or can be assumed based on local resistance patterns, combination therapy with cefazolin plus fosfomycin could be a valuable treatment option for empirical as well as targeted therapy of S. aureus and MRSA infections. Future studies proving the clinical significance of this combination therapy are therefore warranted.